Use of technology to provide mental health services to youth experiencing homelessness: a scoping review protocol - Shalini Lal; Sarah Elias; Vida Sieu; Rossana Peredo (BMJ Open, 2022)
Introduction Despite the importance to address mental health issues as early as possible, youth experiencing homelessness (YEH) often lack prompt and easy access to health services. Recently, there has been a surge of studies focusing on leveraging technology to improve access to mental health services for YEH; however, limited efforts have been made to synthesise this literature, which can have important implications for the planning of mental health service delivery. Thus, this scoping review aims to map and synthesise research on the use of information and communication technologies (ICTs) to provide mental health services and interventions to YEH.Methods and analysis A scoping review of the literature will be conducted, following Arksey and O’Malley’s proposed methodology, the Preferred Reporting Items for Systematic reviews and Meta-Analyses Extension for Scoping Reviews and recent guidelines from the Joanna Briggs Institute. All peer-reviewed papers using ICTs as a means of intervention will be considered, as well as grey literature. Only documents in English or French will be included in the analysis. First, 10 electronic databases will be consulted. Next, all data will be extracted into Covidence. Then, two reviewers will independently conduct the screening and data extraction process, in the case of discrepancies, a third reviewer will be included. Finally, data will be synthesised according to our objectives.Ethics and dissemination Ethics approval is not required, as data will be collected from published literature. Findings will be disseminated through conference presentations and peer-reviewed journals.